Properties of nitrogen fertilization are decisive in determining the effects of elevated atmospheric CO2 on the activity of nitrate reductase in plants. (2nd April 2016) - Zhang, Ranran; Du, Shaoting
ABSTRACT: The concentration of atmospheric CO2 is predicted to double by the end of this century. The response of higher plants to an increase in atmospheric CO2 often includes a change in nitrate reductase (NR) activity. In a recent study, we showed that, under elevated CO2 levels, NR induction in low-nitrate plants and NR inhibition in high-nitrate plants are regulated by nitric oxide (NO) generated via nitric oxide synthases. This finding provides an explanation for the diverse responses of plants to elevated CO2 levels, and suggests that the use of nitrogen fertilizers on soil will have a major influence on the nitrogen assimilation capacity of plants in response to CO2 elevation.